Vitamin D testing in pharmacies: Results of a federal screening campaign - Olaf Rose; Stefanie Eppacher; Johanna Pachmayr; Stephanie Clemens (Exploratory Research in Clinical and Social Pharmacy)
Introduction: The convenient accessibility of pharmacies positions them as optimal venues for screening initiatives. There is growing public concern regarding vitamin D levels, particularly during the winter months in middle-and northern latitudes. This study aimed to assess vitamin D levels in early spring and to evaluate the feasibility of implementing a large-scale screening campaign within pharmacies. Methods: This investigation was structured as a cross-sectional multicenter survey conducted in a routine care setting. Data collection was performed in a fully anonymized manner. An automatic fluorescent immunoassay system was utilized for point-of-care-testing, and both patient and provider questionnaires were developed. Quantitative data were analyzed descriptively. Both parametric- and nonparametric statistical tests were performed to analyze the data, ensuring robust results across different assumptions. A resulting maturity matrix for implementation was conceptualized. Results: Over a two-week campaign, 62 community pharmacies conducted a total of 2770 vitamin D tests. All participants completed the questionnaire, and 45 pharmacists participated in a retrospective survey. Vitamin D deficiency was identified in 56.2 % of participants, while 25.2 % exhibited levels of insufficiency. A higher BMI was associated with lower vitamin D levels, whereas daily supplementation correlated with higher levels compared to intermittent or weekly dosing regimens. The vast majority of patients expressed high satisfaction with the services provided. Pharmacists valued the positive feedback from patients and expressed enthusiasm for further testing and the advancement of clinical pharmacy services. The resulting maturity matrix facilitates corporate implementation. Conclusion: The implementation of a large-scale federal vitamin D screening campaign proved to be feasible and resulted in high levels of satisfaction among both patients and providers. The findings indicated significantly low vitamin D levels among participants. Pharmacists expressed a desire for an expansion of clinical pharmacy services in the future.Vitamin D testing in pharmacies: results of a federal screening campaign.